2004
DOI: 10.1016/j.otohns.2004.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Flutamide as a Preoperative Treatment in Juvenile Angiofibroma (JA) with Intracranial Invasion: Report of 7 Cases

Abstract: Despite the fact that there is a report of the efficacy of flutamide in the literature, we did not find advantages in using it in patients with JA. However, and due to the very small number of patients enrolled, we think that more studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 10 publications
0
39
0
1
Order By: Relevance
“…However, it is of particular interest in partial volume reduction. [14][15][16] None of the patients in this study had adjunctive therapy for tumour size reduction. Anaesthesiologists must be aware of these treatment modalities and their side-effects.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is of particular interest in partial volume reduction. [14][15][16] None of the patients in this study had adjunctive therapy for tumour size reduction. Anaesthesiologists must be aware of these treatment modalities and their side-effects.…”
Section: Discussionmentioning
confidence: 97%
“…Patients treated with antiandrogenic medications, principally Flutamide, experienced significant side effects including gynecomastia and other feminization features [21], and given the usual association with The age of the patients in this series ranged from 8 to 27 years, with a mean of 14.7 years, slightly younger than the reported average (17 years) [1]. According to the literature, the diagnosis of NAF is uncommon over the age of 25, and we had only 1 patient 27 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical literature regarding the use of Flutamide is limited to two studies and 11 cases. Gates et al [7] observed an average tumor reduction of 44% in 4 of 5 cases receiving a 6 week treatment course, and Labra et al [8] observed a maximum tumor reduction of only 11.1% in 6 cases receiving a 3 week treatment course. Currently recommendation include 6 week course of flutamide as adjuvant therapy in the post-pubertal patient, so as to bring about presurgical volume shrinkage and facilitate surgical excision.…”
Section: Hormonal Therapymentioning
confidence: 99%
“…So, hormonal therapy in form of androgens and estrogens has been tried in the past. Two reports are there in the literature using flutamide, an antiandrogen compound to decrease the tumor volume [7,8].…”
Section: Treatmentmentioning
confidence: 99%